Longitudinal association between emotion‐related parenting behavior and child aggression: The moderating role of parent‐child physiological synchrony. Issue 3 (30th December 2020) - Ahemaitijiang, Nigela; Ren, Haining; Wang, Hui; Han, Zhuo Rachel
Abstract: Considering the high prevalence of aggressive problems found in middle childhood and their negative impacts on children's overall adjustment, it is important to explore factors that may give rise to childhood aggression, as well as the underlying mechanisms involved within the family context. Applying a biopsychosocial approach, the aim of our study was to examine the relations between emotion‐related parenting behavior (ERPB, e.g., parental psychological control and parental emotion dysregulation) and childhood aggression with a focus on the potential moderating effects of parent‐child physiological synchrony on these relations. Eighty‐nine parent‐child dyads (total N = 178) participated in the study (child M age = 8.76 years, SD = 1.81 years, 49 boys). At T1, ERPB was observed and coded from dyadic interaction and parent‐child physiological synchrony was assessed using interbeat interval (IBI) calculated from the participant's heart rate (HR) during an interaction task. Parents also reported their child's aggressive behavior at T1 and 9 months later (T2). The results showed that for children demonstrating stronger physiological synchrony with their parents, higher levels of parental psychological control and parental emotion dysregulation predicted their more aggressive behavior. Our findings suggest that for certain negative types of ERPB, parent‐child physiological synchrony seems to be a risk factor for the development of children's aggressive behavior.